Fire tests with lithium-ion battery electric vehicles in road tunnels. (December 2022) - Sturm, Peter; Fößleitner, Patrik; Fruhwirt, Daniel; Galler, Robert; Wenighofer, Robert; Heindl, Simon Franz; Krausbar, Stefan; Heger, Oliver
Abstract: Alternative propulsion technologies, including battery-electric vehicles, are becoming increasingly prevalent. Whilst such vehicles remain a small overall proportion of the vehicle fleet, the combined impact of government policy and technological advances in alternative fuels is expected to accelerate the increase in their numbers in coming years. As a result of these changes, the nature of tunnel safety risk (including the risk of fire) is expected to change over time. The risk implications associated with such vehicles thus requires more detailed consideration. This entails evaluation of incident consequences with particular attention being paid to the impact of fire characteristics and toxic emissions on tunnel users and to the need for specific emergency intervention strategies. In the past, concerns were voiced with respect to the fire safety of the new energy storage device (battery) and the possibility of more difficult firefighting conditions. This resulted in a series of investigations concerning the safety aspects of batteries and battery electric vehicles. However, most of the tests performed merely dealt with battery cells or battery packs. To date, publicly available tests involving actual vehicles remain relatively rare. In 2018, the Austrian Government commissioned a research project concerning the effect of incidents with battery electric vehicles on tunnel safety. This project encompassed fire tests of passenger cars, simulations for heavy duty vehicles, and the impact of incidents with such vehicles on the safety of tunnel users and the tunnel structure. In a series of fire tests, the heat-release and production of (toxic) substances has been evaluated. The burning behaviour of vehicles with different energy storage technologies (i.e. Li-ion batteries, Diesel) was monitored and compared to each other. The heat-release rate and emission of (toxic) substances was measured, and different fire-fighting methods were applied during each test. This paper will focus on the aspect of full-scale fire tests of passenger cars performed in a road tunnel. It should be emphasized that the battery-electric vehicle fire tests presented here were the first of their kind under real road tunnel conditions. This concerns the fire behaviour, but also some new approaches to fighting a BEV fire. All previous tests reported in journals were either carried out in fire halls or only concerned individual battery modules. Graphical abstract: Fire test of a battery electric vehicle (model year 2020) with an 80 kWh battery. At 850s after fire starts the battery got fully involved in the fire. This is visible by a rapid breakdown of the voltage (red line) from 400 V to zero and a constant increase of the temperature inside the battery from ambient temperature up to 400 °C. At 1260 s a fire lance injected water directly into the battery casing which resulted in a rapid reduction of the core temperature of the battery from 420 °C to 100 °C. Image 1 Highlights: Full scale fire tests of battery electric vehicles in road tunnels under real world conditions. Investigations of toxic gases, heat release rate and water and surface pollution. Compared to conventional car fires the maximum heat release rate may increase considerably as soon as the battery is fully involved into the fire. Fire-fighting investigations showed that the use of fire lances to directly introduce water into the battery case is very efficient, fire blankets could not be used successfully. Full data repository concerning all test parameters publicly available for further analysis and validation.